Synergistic aspect analysis of the organization adaptation to changes in the environment through a portfolio of projects - Молоканова, Валентина Михайлівна (Eastern-European Journal of Enterprise Technologies, 2015)
The possibility of applying the general provisions of synergy, as an integrative discipline, to the methodology for the organization development management through portfolios of projects was considered. Comparative analysis of the traditional classical and synergistic approaches to the evolutionary development of systems was given. The concept of bifurcations in development systems, as sudden and unexpected changes in organizational processes, was examined. Methodological principles of monitoring the organization development portfolio, which provide ongoing control of the organization development progress within established deviations of the defined indicators were presented. The cases of growth of internal entropy of the system and loss of property of adaptation to the environment based on a system approach were reviewed. Application of value approach to synergistic organization development management based on investigating the indicators of the organization adaptation to changes in the environment was proposed. The algorithm of using the synergistic management for evolutionary organization development were presented, control calculations to analyze the results on the example of the operating enterprise were conducted.